Análisis del Impacto de las Estrategias de Marketing Digital en la Red Social Instagram de la Marca The Monkey Shop en Quito en 2023. - Romero Herrera, Ariel Alejandro (2024)
The growth of digital media has generated great interest in understanding the best tools for its use and, above all, how to correctly transmit messages to the audience. The present research aims to analyze the impact of the correct use of digital marketing strategies on the social network Instagram through the case study The Monkey Shop 2023, through a data collection with a mixed approach, that is, quantifiable data on the impact that the brand's Instagram account has on its audience and qualitative findings collected through bibliographies and interviews with experts. Among the most important findings, it was found that it is necessary to take into account aspects such as good storytelling, the humanization of the brand and database management to position a brand on the Instagram social network. Regarding the strategies for obtaining results converted into sales, it is mentioned that the most effective alternative is the Target Guideline, which, together with the correct segmentation of the public, the detection of interests and keywords, demographic data, ages and gender, can quickly generate a return on investment when sharing ads. In conclusion, this report has a wide variety of important data in the context of Digital Marketing, prioritizing strategies, trends and the impact on the public. Likewise, this content is intended for those interested in positioning their brand on networks, as well as for small businesses that are starting in the world of digital platforms. Key words: audience, guideline, data base, humanization of the brand, digital marketing strategies.